INFLUENCE THE INFLUENCE OF THE COOPERATIVE LEARNING MODEL ON CRAWL STYLE SWIMMING LEARNING OUTCOMES VIEWED FROM MOTIVATION IN CLASS X STUDENTS OF SMA NEGERI 1 ABIANSEMAL: crawl learning outcomes, Student Teams Achievement Divisions (STAD), motivation - Budi Rianita, Ni Putu Pande; Sudiana, I Ketut; Hidayat, Syarif (Jurnal Speed (Sport, Physical Education, Empowerment), 2023)
Jenis riset ini ialah eksperimen sungguhan dengan rancangan riset treatment by level. Riset ini bertujuannya buat mengetahui besarnya pengaruh model pembelajaran kooperatif terhadap motivasi belajar renang gaya crawl pada peserta didik kelas X SMA Negeri 1 Abiansemal tahun pelajaran 2022/2023. Populasi riset ini ialah seluruh peserta didik kelas X SMA Negeri 1 Abiansemal tahun pelajaran 2022/2023 yang bertotal 355 siswa. Sebanyaknya 70 siswa dipilah jadi sampel yang ditentukan dengan teknik random sampling. Data hasil belajar dihimpunkan lewat tes objektif dan unjuk kerja, sebaliknya data motivasi dihimpunkan lewat kuesioner. Data dianalisis dengan memakai ANOVA dua jalur berbantuankan SPSS 17.00 for windows. Hasil riset menampakkan ialah Pertama adanya perbedaannya hasil belajar yang signifikan antara peserta didik yang mengikuti model pembelajaran kooperatif tipe STAD berbantuankan video dan peserta didik yang mengikuti model pembelajaran kooperatif tipe STAD, Kedua adanya interaksinya yang sifnifikan antara model pembelajaran dan motivasi terhadap hasil belajar, Ketiga adanya perbedaannya yang signifikan hasil belajar peserta didik yang mengikuti model pembelajaran kooperatif tipe STAD berbantuankan video dan model pembelajaran kooperatif tipe STAD pada kategori motivasi tinggi, dan Keempat adanya perbedaannya yang signifikan hasil belajar peserta didik yang mengikuti model pembelajaran kooperatif tipe STAD berbantuankan video dan model pembelajaran kooperatif tipe STAD pada kategori motivasi rendah. Kata kunci: hasil belajar, model pembelajaran kooperatif, motivasi   ABSTRACT This type of research is a real experiment with a treatment by level research design. This research aims to determine the magnitude of the influence of the cooperative learning model on the motivation to learn crawl style swimming in class X students at SMA Negeri 1 Abiansemal for the 2022/2023 academic year. The population of this research is all students in class A total of 70 students were selected into samples determined using random sampling techniques. Learning outcome data is collected through objective tests and performance, whereas motivation data is collected through questionnaires. Data were analyzed using two-way ANOVA assisted by SPSS 17.00 for Windows. The results of the research show that First, there is a significant difference in learning outcomes between students who follow the video-assisted STAD type cooperative learning model and students who follow the STAD type cooperative learning model, Second, there is a significant interaction between the learning model and motivation on learning outcomes, Third, there is there is a significant difference in the learning outcomes of students who follow the video-assisted STAD type cooperative learning model and the STAD type cooperative learning model in the high motivation category, and Fourth, there is a significant difference in the learning outcomes of students who follow the video-assisted STAD type cooperative learning model and the video-assisted cooperative learning model STAD type in the low motivation category Keywords: learning outcomes, cooperative learning model, motivation